AduLeT project and its community of practice: an insight into technology advanced use within higher education - Gonçalves, Vitor (2019)
For the last two decades one cannot overlook the fact that there have been major improvements in the area of educational technology. Schools and universities also try to accompany the evolutional pace of this new technological stance introduced in the teaching-learning process. The spread of tablets, smartphones and social networks has accounted for an immersion into the technological world by both students and lecturers. Hence, it has been most impossible to underestimate the value of these tools regarding teaching methods. On the one hand, students, as digital natives, adhere enthusiastically to these new teaching approaches. On the other, lecturers are sometimes bereft of ideas when it comes to motivating the students and introduce innovative methodologies to their in regard to the use of technologies in an advanced way. The aim of this paper is to present the platform Community of Practice (CoP), the ultimate visible result of the Advanced use of Learning Technologies in higher education (AduLeT) project, a collaborative 3-year (2016-2019) research project funded by the European Commission, involving seven partner countries. CoP meets the standards that teaching nowadays requires aiming at providing higher education lecturers with a substantial matrix of tools and methods combined. We shall demonstrate the use and effectiveness of the CoP by showing some practical examples and by highlighting several insightful user experiences within the Portuguese higher education context. To establish a connection with the main target audience, we organized two workshops and a multiplier event to lecturers from several higher education institutions, disseminating the results and involving more lecturers in this community. Thus, we intend to materialize in this paper a summary of the project, essentially in the Portuguese perspective. During the multiplier event, we had very positive reactions from the lecturers regarding the CoP. After this event, the participants were also asked to fill in a satisfaction survey on the use of the CoP. In the paper, we shall then put forth and analyze the survey answers so that we shed some light on the efficacy and applicability of the CoP.